2021
DOI: 10.2147/ijgm.s304449
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Parameters Predict Short- and Long-Term Adverse Cardiovascular Events in Patients with Acute Myocardial Infarction

Abstract: Objective This study aimed to find echocardiographic parameters that can predict short- and long-term adverse cardiovascular events in patients with AMI. Methods A total of 126 patients with AMI admitted to our hospital from July to December 2012 were enrolled in this study. All patients underwent echocardiographic examination within 12 hours after admission and received regular follow-ups until December 2018. The primary endpoint was a composite of the major adverse ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…When coronary artery lesions were divided into the culprit lesions of AMI and the non-AMI lesions, the clinical outcomes following PCI were worse in the culprit lesions of AMI than in the non-AMI lesions 3,4) . However, since the clinical outcomes vary widely among the culprit lesions of AMI 5) , a simple risk marker would be needed to stratify long-term outcomes following PCI to the culprit lesions of AMI. Although there are several risk markers regarding the clinical outcomes of patients with AMI 6,7) , simple risk markers that were derived from coronary angiography (CAG) have not been fully proposed.…”
Section: Introductionmentioning
confidence: 99%
“…When coronary artery lesions were divided into the culprit lesions of AMI and the non-AMI lesions, the clinical outcomes following PCI were worse in the culprit lesions of AMI than in the non-AMI lesions 3,4) . However, since the clinical outcomes vary widely among the culprit lesions of AMI 5) , a simple risk marker would be needed to stratify long-term outcomes following PCI to the culprit lesions of AMI. Although there are several risk markers regarding the clinical outcomes of patients with AMI 6,7) , simple risk markers that were derived from coronary angiography (CAG) have not been fully proposed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have shown that the left ventricle wall motion score index (WMSI) is a reliable measure of reperfusion success in patients with acute STEMI (3)(4)(5) and could predict the short and long-term prognosis of these patients (6,7). Also, as a surrogate of infarct size, WMSI could be used for myocardial remodeling assessment even better than left ventricular ejection fraction (LVEF) (4).…”
Section: Introductionmentioning
confidence: 99%
“…4 The measurement of MACEs in cases receiving revascularization has also benefited from the use of wall motion scores (WMSs). 5,6 Subsequent studies have assessed the relevance of the WMS in predicting MACEs in patients having PCI, and the degree of left ventricular function impairment has also been linked to unfavourable cardiovascular events. It is still not clear if using a measure that combines the WMS and SSII would help predict outcomes for people getting PCI because it has not been studied well.…”
Section: Introductionmentioning
confidence: 99%
“…It is still not clear if using a measure that combines the WMS and SSII would help predict outcomes for people getting PCI because it has not been studied well. 5,6 The left ventricle is separated into several segments in the 17-segment model, which is then used to compute the WMS in accordance with the advice of the American Society of Echocardiography. 7 Each segment's contractility is graded using the following system: Normal is number one, followed by hypokinesia, dyskinesia, akinesia, and ventricular aneurysm.…”
Section: Introductionmentioning
confidence: 99%